Similar Survival Between Non-Western Immigrant Patients and Danish-Born Patients with Lymphoma: A Danish Population-Based Study - Simonsen MR; Maksten EF; Jakobsen LH; Severinsen MT; Dann EJ; Frederiksen H; Niemann CU; Jørgensen JM; Clausen MR; Starklint J; Johnsen SP; El-Galaly TC; et al. (Clinical Epidemiology)
Mikkel Runason Simonsen,1,2 Eva Futtrup Maksten,1,3 Lasse Hjort Jakobsen,1 Marianne Tang Severinsen,1,3 Eldad J Dann,4 Henrik Frederiksen,5,6 Carsten Utoft Niemann,7 Judit Mészáros Jørgensen,8 Michael Roost Clausen,9 Jørn Starklint,10 Søren Paaske Johnsen,11 Tarec Christoffer El-Galaly,1,3,5,12 Joachim Baech1,13 1Department of Hematology, Clinical Cancer Research Center, Aalborg University Hospital, Aalborg, Denmark; 2Department of Mathematical Sciences, Aalborg University, Aalborg, Denmark; 3Department of Clinical Medicine, Aalborg University, Aalborg, Denmark; 4Department of Haematology, Rambam Medical Center, and Bruce Rappaport Faculty of Medicine, Technion -Israel Institute of Technology, Haifa, Israel; 5Department of Hematology, Odense University Hospital, Odense, Denmark; 6Academy of Geriatric Cancer Research (Agecare), Odense University Hospital, Odense, Denmark; 7Department of Hematology, Rigshospitalet, Copenhagen University Hospital, Copenhagen, Denmark; 8Department of Hematology, Aarhus University Hospital, Aarhus, Denmark; 9Department of Hematology, Vejle Hospital, Vejle, Denmark; 10Department of Medicine: Hematology, Goedstrup Hospital, Goedstrup, Denmark; 11Danish Center for Health Services Research, Department of Clinical Medicine, Aalborg University and Aalborg University Hospital, Aalborg, Denmark; 12Department of Medicine Solna, Clinical Epidemiology Division, Karolinska Institutet, Stockholm, Sweden; 13Department of Clinical Biochemistry, Aalborg University Hospital, Aalborg, DenmarkCorrespondence: Mikkel Runason Simonsen, Email Mikkel.simonsen@rn.dkPurpose: This nationwide Danish cohort study compared overall survival (OS) between non-Western immigrant patients and Danish-born patients with lymphoma in Denmark. Furthermore, differences in clinical and socioeconomic variables were compared, and mediators of OS differences were explored to explain possible outcome differences.Patients and Methods: The study included a total of 540 non-Western patients and 16,294 Danish-born patients diagnosed with lymphoma in the period 2000– 2020. Inverse probability weighting and mediation analysis using a natural effects Cox model were used to investigate the causal relationship between immigration status and OS.Results: Indirect effects mediated through differences in performance status and income indicated a trend towards inferior OS for non-Western immigrant patients with HRs of 1.06 (0.99– 1.14) and 1.06 (0.99– 1.14). However, no total causal effect of immigration status on OS was observed overall (HR: 0.94 [0.79– 1.12]) and within subtype-specific analyses, except for classical Hodgkin lymphoma.Conclusion: No significant differences in OS between non-Western immigrant patients and Danish-born patients were discovered.Plain Language Summary: Non-Western immigrant lymphoma patients in Western countries may face multiple challenges, including lower socioeconomic status and insufficient language proficiency, which can make navigating the complexity of modern lymphoma treatment difficult. This study investigated whether the Danish tax-based healthcare system has overcome these challenges and delivered non-Western immigrant patients quality care on the same levels as that of the Danish-born patients.Therefore, using available population based Danish registries, survival between these groups were compared, while adjusting for important clinical differences, and no significant effect of immigration status on survival was found even though non-Western immigrant patients generally had lower socioeconomic status.Keywords: epidemiology, socioeconomics, causal inference, mediation analysis